Income distribution in macroeconomic models - Bertola Giuseppe; Foellmi Reto; Zweimuller Josef (Princeton Princeton Univ Press, 2006)
This book looks at the distribution of income and wealth and the effects that this has on the macroeconomy, and vice versa. Is a more equal distribution of income beneficial or harmful for macroeconomic growth, and how does the distribution of wealth evo
Keywords: Econometric models; Economic development; Equality; Income distribution; Wealth